2016
DOI: 10.4067/s0718-16202016000300003
|View full text |Cite
|
Sign up to set email alerts
|

CHARACTERIZATION OF RESISTANCE EXPRESSION IN GENOTYPES OF SOLANUM SECTION LYCOPERSICON AGAINST Tuta absoluta (LEPIDOPTERA: GELECHIIDAE)

Abstract: N. Vitta, P. Estay, and Chorbadjian, R.A. 2016. Characterization of resistance expression in genotypes of Solanum Section Lycopersicon against Tuta absoluta (Lepidoptera: Gelechiidae). Cien. Inv. Agr. 43(3):366-373. Two studies were conducted with the aim of characterizing the antixenosis and antibiosis resistance expression of genotypes in the Solanum section Lycopersicon against Tuta absoluta (Meyrick). The species used were S. lycopersicum (Fiorentino, Naomi and Belle), S. habrochaites (RCAT030597, PI126446… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…The results showed significant dif- (Stam et al 2017). In their study, Vitta et al (2016) reported that S. chilense had the highest larval survival of T. absoluta among the tomato species. However, they also determined that S. chilense was resistant to T. absoluta.…”
Section: Discussionmentioning
confidence: 93%
“…The results showed significant dif- (Stam et al 2017). In their study, Vitta et al (2016) reported that S. chilense had the highest larval survival of T. absoluta among the tomato species. However, they also determined that S. chilense was resistant to T. absoluta.…”
Section: Discussionmentioning
confidence: 93%
“…Another study determined the level of resistance among tomato cultivars based on the antibiosis (by observing larval survival and weight of male, females pupae) and antixenosis (by observing oviposition) criteria (Vitta et al, 2016). Among the wild varieties evaluated, S. habrochaites (RCAT030597) genotype was found resistant based on the antibiosis with lower larval survival.…”
Section: Resultsmentioning
confidence: 99%
“…This higher preference for oviposition on tomato and potato has been explained in terms of the volatile organic compounds that deter oviposition on eggplant and the presence of higher amounts of terpenes in those plant species compared to eggplant that serve as oviposition stimulants [ 46 ]. In addition, the lower suitability of eggplant for infestation by T. absoluta has been explained in terms of the presence of 77 secondary metabolites that increase in abundance following infestations that are believed to deter feeding by T. absoluta [ 47 ]. Thus, the lower feeding damage by T. absoluta on eggplant is due to antixenosis (defined as the non-preference of insect pests for plants that lack stimuli for feeding or oviposition) and antibiosis (defined as adverse physiological responses experienced by the insect pest following the ingestion of plant material) resistance.…”
Section: Discussionmentioning
confidence: 99%